The Influence of Work Design and Discipline on the Performance of Non ASN Employees with Job Satisfaction as an Intervening Variable in the Protocol and Communication Section of The Leadership Regional Secretariat of Medan City - Fithrya, Nita; Rahayu, Sri (Ridwan Institute, 2026)
This study aims to analyze the influence of work design and work discipline on the performance of Non-ASN employees, with job satisfaction as an intervening variable, in the Protocol and Communication Section of the Medan City Regional Secretariat Leadership. The research was motivated by the phenomenon of suboptimal performance among Non-ASN employees, characterized by delays in completing tasks, low initiative, and declining job satisfaction due to disproportionate workloads and unclear task distribution. Using a quantitative approach with an explanatory research method, data were collected from all Non-ASN employees through a census sampling technique. Questionnaires were distributed, and data were analyzed using path analysis assisted by statistical software. The results revealed that work design and work discipline positively and significantly affect employee performance. Job satisfaction was also proven to play an intervening role, strengthening the influence of both work design and work discipline on performance. Specifically, work discipline (X2) positively affects job satisfaction (Z) with a path coefficient of 0.304 (p = 0.003) and employee performance (Y) with a coefficient of 0.254 (p = 0.005). Job satisfaction (Z) significantly affects employee performance (Y) with a coefficient of 1.075 (p = 0.001). Similarly, work design (X1) positively influences job satisfaction (Z) with a coefficient of 0.365 (p = 0.003) and performance (Y) with a coefficient of 0.288 (p = 0.001). Mediation analysis confirmed that job satisfaction significantly mediates the relationship between both work design and work discipline on performance (p < 0.05). These findings emphasize that effective work planning and disciplined behavior are essential to enhance job satisfaction and improve employee performance.